The Effect of Cabri Express in Geometry Learning on Students' Mathematical Communication Ability - Tamur, Maximus; Weinhandl, Robert; Sennen, Eliterius; Ndiung, Sabina; Nurjaman, Adi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Cabri is characterized by an attractive advantage and provides wide-ranging benefits in the teaching of mathematics. Although today there have been many studies on the edges of Cabri, experiments on Cabri-Express have not been widely explored. For this reason, a quasi-experimental study with a randomized posttest only design involving 80 grade VII junior high school students in Ruteng, Indonesia, was conducted to analyze the effect of Cabri-Express in learning geometry on students' overall mathematical communication ability (MCA) and based on students' initial mathematical abilities. The results of the MCA test are the research data, which consists of 5 questions that are then analyzed by t-test and preceded by conducting an analysis prerequisite test. The Hedges equation describes how much influence the Cabri-Express model has on students' MCA. The results showed that the overall MCA of students who were taught using the help of an Cabri-Express was better than students who were taught using the conventional model. From the Hedges equation, an effect size of 1.23 is obtained, indicating that the use of Cabri-Expresses strongly affects students' MCA. These results interpret that students who are ranked 13th in the experimental class are equivalent to those who are ranked 5th in the control class. By clarifying the effect of Cabri-Express on students' MCA, this study recommends the need to use Cabri-Express in mathematics classes. The analysis results can also help researchers explore other material in a relatable context.